PID Controller with Enhanced Disturbance Rejection - Zlosnikas, V.; Baskys, A. (Elektronika ir Elektrotechnika, 2008)
The Proportional – Integral – Derivative (PID) controller with the enhanced load disturbance rejection has been suggested. The algorithm of control in this controller employs different values of controller parameters during the set point change response and load disturbance response of the control system. The controller parameters are switched when the sign of the error changes. This feature allows us to increase the degree of freedom during tuning of the controller to the plant. The tuning technique of the controller is the same as that used for the conventional PID controller. The results of the investigation of the concrete control system based on the developed controller show that proposed PID controller in contrast to the conventional one allows us to improve the positive load disturbance rejection of the control system not sacrificing the set point response dynamics. In case of the negative load disturbance the proposed modification of the PID controller does not have advantage over the conventional PID. Ill. 3, bibl. 8 (in English; summaries in English, Russian and Lithuanian).